Subjective aspect of quality of life of patients with diabetes mellitus - Živanović Srđan; Kulić Veselinka; Hadživukuvić Natalija; Pavlović Jelena; Matović Sandra; Vasiljević Marija; Despotović Mile (Association of Nurses Technicians and Midwives, 2022)
Introduction: Diabetes mellitus (DM) is a global public health problem. It is a complex illness which affects on the medical, psychological and social aspects of life. The aims of this research were to determine the subjective sense quality of life of patients with diabetes mellitus, to determine whether or not there are differences in the quality of life of patients with diabetes mellitus compared to sex, age and place of residence, as well as to determine factors the quality of life of patients with DM. Material and methods: The study was conducted as a crosssectional study of the population of persons with (DM). The sample consisted of 100 respondents, who in the observed period were treated at the Department of Internal Medicine of the University Hospital in Foča. A combined questionnaire consisting of 40 questions was used. The questions in the questionnaire were related to socio-demographic characteristics, hobbies, support of family and friends of patients, eating habits, as well as the presence of comorbidities. The HolmesRahe Stress Scale and the Subjective Assessment of Well-Being Scale (SVB Life Satisfaction Scale) were also included in the questionnaire. Results: Among the respondents there were 48 (48%) men and 52 (52%) women. Respondents rated their satisfaction with the quality of life, with an average score of 6.68 ± 1.72. Younger respondents have significantly better quality of life (7.09 ± 1.91) compared to the older group of subjects 6.35 ± 1.50. Also, respondents who living in the city are significantly satisfied with their quality of life (6.95 ± 1.80) compared to respondents who lives in the countryside (6.14 ± 1.45). Respondents with secondary education (30%) are significantly satisfied with their quality of life compared to respondents without primary school (13%), with elementary school (3%) or with higher education (12%). Conclusion: People with diabetes their own quality of life estimates with satisfactory grades.